Let a be the first term in the sequence, and d the common difference between consecutive terms. If aₙ denotes the n-th term in the sequence, then
a₁ = a
a₂ = a₁ + d = a + d
a₃ = a₂ + d = a + 2d
a₄ = a₃ + d = a + 3d
and so on, up to the n-th term
aₙ = a + (n - 1) d
The sum of the first 10 terms is 100, and so
![\displaystyle \sum_(n=1)^(10) a_n = 100 \\ \sum_(n=1)^(10) (a + (n-1)d) = 100 \\ (a-d) \sum_(n=1)^(10) 1 + d \sum_(n=1)^(10) n = 100 \\ 10a+45d = 100](https://img.qammunity.org/2023/formulas/mathematics/college/gusau4ux7ddgkjvxllctbkb2biaw4vawty.png)
where we use the well-known sum formulas,
![\displaystyle \sum_(n=1)^N 1 = 1 + 1 + 1 + \cdots + 1 = N](https://img.qammunity.org/2023/formulas/mathematics/college/8wdkjliv24etxpewgmtcy9cdqgxqdetcjr.png)
![\displaystyle \sum_(n=1)^N n = 1 + 2 + 3 + \cdots + N = \frac{N(N+1)}2](https://img.qammunity.org/2023/formulas/mathematics/college/inuz0fyp8omu4aeaj5cx35qrcjwaexe6v8.png)
The sum of the next 10 terms is 300, so
![\displaystyle \sum_(n=11)^(20) a_n = 300 \\ (a-d) \sum_(n=11)^(20) 1 + d \sum_(n=11)^(20) n = 300 \\ (a-d) \left(\sum_(n=1)^(20) 1 - \sum_(n=1)^(10) 1\right) 1 + d \left(\sum_(n=1)^(20) n - \sum_(n=1)^(10) n\right) = 300 \\ 10a+145d = 300](https://img.qammunity.org/2023/formulas/mathematics/college/bvbfiaf9p3c28ymlc4uexh3xnahzrmn9kz.png)
Solve for a and d. Eliminating a gives
(10a + 145d) - (10a + 45d) = 300 - 100
100d = 200
d = 2
and solving for a gives
10a + 145×2 = 300
10a = 10
a = 1
So, the given sequence is simply the sequence of positive odd integers,
{1, 3, 5, 7, 9, …}
given recursively by the relation
![\begin{cases}a_1 = 1 \\ a_n = a_(n-1) + 2 & \text{for }n>1\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/z0won9hkqy84wnqsdsk5zbwnt0t3s169z0.png)
and explicitly by
![a_n = 1 + 2(n-1) = 2n - 1](https://img.qammunity.org/2023/formulas/mathematics/college/4kl7p6qbyjsef8utt27rg0412pqypjdnvg.png)
for n ≥ 1.